Dancing to the top: How collective action revitalized arts education in Boston. Issue 4 (2nd October 2018) - Gibson, Cynthia M.
ABSTRACT: In 2009, a group of local foundations, the school district, arts organizations, and the Mayor's Office launched the Boston Public Schools Arts Education Initiative (BPS-AE)—a multiyear, citywide, public–private initiative aimed at increasing BPS students' access to in-school arts education. Managed by a strong local intermediary with deep experience in education, this initiative used several complementary, overlaid strategies: direct service, system building, and community engagement—all of which were supported by a philanthropic collaborative of local and national funders. Today, 17, 000 more BPS students receive arts education; nearly 130 additional full-time certified arts teachers have been hired; and district spending on arts has risen to 26 million annually, compared to 15 million in 2009. There is also growing demand from the larger community for more and better arts education. In 2015, BPS-AE produced a case study that provides a more detailed explication of the multitiered strategy it used to achieve these results. The study offers recommendations as to how other cities can involve diverse key constituencies to advance this kind of initiative, create leadership structures that support effective citywide collaboration, engage community stakeholders in participatory planning processes, leverage private philanthropy to boost public funding, and develop a centralized support system for school principals and arts teachers.